PROFIL PASIEN STROKE PADA 25 RUMAH SAKITDI SUMATERA UTARA 2012 SURVEI BERBASIS RUMAH SAKIT - Aldy S. Rambe, Aida Fithrie, Iskandar Nasution, Tonam (NEURONA, 2013)
INTRODUCTION STROKE IS ONE OF NEUROLOGICAL SYNDROME WHICH POSE THE LARGEST THREAT ON CAUSING DISABILITY IN HUMAN LIFE IN INDONESIA NATIONAL STROKE DATA SHOWS STROKE AS THE HIGHEST CAUSE OF MORTALITY IN HOSPITAL 154 TO OUR KNOWLEDGE THERE IS NO AVAILABLE DATA ON STROKE PATIENTS PROFILE IN NORTH SUMATERA